Life after default: Credit hardship and its effects - Giacomo De Giorgi; Costanza Naguib (University of Bern, Department of Economics, 2022)
We analyze the impact of credit default on individual trajectories. Using a proprietary dataset for the years 2004-2020, we find that after default individuals relocate to cheaper areas. Importantly, default has long-lasting negative effects on income, credit score, total credit limit, and home-ownership status.AWe analyze the impact of credit default on individual trajectories. Using a proprietary dataset for the years 2004-2020, we find that after default individuals relocate to cheaper areas. Importantly, default has long-lasting negative effects on income, credit score, total credit limit, and home-ownership status.
Keywords: J61; G51; D12; 330; mobility; bankruptcy; default; credit; income